The fifth gospel [large type] : a novel - Caldwell, Ian, 1976- (Thorndike Press, 2015)
A lost gospel, a contentious relic, and a dying pope's final wish converge to send two brothers--both Vatican priests--on an intellectual quest to untangle Christianity's greatest historical mystery.